Ma'had Aly Madarijul Ulum Education Management in Organizing Education Based on the Qur'an and Kitab Kuning - Isma Kamila; Subandi; Amiruddin (CV. Creative Tugu Pena, 2025)
This study explores the educational management of Ma’had Aly Madarijul ‘Ulum in Bandar Lampung in implementing a curriculum rooted in the Qur'an and classical Islamic texts (kitab kuning). The primary focus is on examining how planning, implementation, and supervision are conducted to ensure effective institutional governance. Employing a qualitative case study approach, data were collected through observations, in-depth interviews with administrators and educators, as well as document analysis of institutional policies and administrative systems. The findings reveal that educational planning is carried out systematically through curriculum development, recruitment of competent educators, and the management of supporting infrastructure. Implementation is characterized by a traditional pesantren-based administrative system that emphasizes efficiency and strong coordination among administrators, educators, and students. Supervision is conducted through routine evaluations of both managerial performance and policy execution. However, the study also identifies challenges, particularly in the areas of monitoring systems and resource management, which have yet to reach optimal functionality. These insights contribute significantly to the development of an educational management model for Islamic higher education institutions. Recommendations include enhancing data-driven supervision systems, strengthening managerial capacities, and integrating technology into administrative processes to ensure sustainable and professional institutional governance. With continuous improvement, Ma’had Aly Madarijul ‘Ulum holds the potential to become a leading, adaptive, and competitive Islamic higher education institution.